Applied knowledge test for the MRCGP questions and answers for the AKT - A-Ali, Nuzhet (Scion Publishing Limited, 2014)
This much expanded third edition features nearly 500 questions in all the formats used in the AKT paper. The questions are based on everyday practice scenarios, and new questions have been added which cover those topics which the RCGP has identified as causing particular problems for candidates